The Sharing Economy as a Model 5.0 for Developing an Innovative Strategy of Universities - Narymen Benrachou (Journal of North African Economies, 2025)
The study aims to develop a set of methodological methods and tools to form an effective adaptive strategy for the international competitiveness of the University in the digital age. The analytical method was used allowing to study the characteristics of the management system and the management subsystem innovation and digitization in the dynamics of continuous development, in the interconnection and interaction with the environment factors of the work and development of the University, reaching the main results that determine the following scientific novelty: The concept of transformation of the university into the digital age, which involves a constant transition from resource management to management, firstly, expands the category of resource management by including the intangible and the number of external network resources in its composition, secondly, the speed of reaction to the transformations occurring in the external environment, which is considered the main criterion, and finally, management methods change according to the concept of Open Science and through the infrastructure of the University stakeholders (student, teacher, researcher).